A Gly684Ala substitution in the androgen receptor is the cause for azoospermia in a Chinese family with mild androgen insensitivity syndrome and normal hormone levels - Yuan, Yuan; Xu, Wen-Qing; Chen, Ying; Luo, Tao; Chen, Hou-Yang (Frontiers in Genetics, 2022)
Androgen receptor gene (AR) is essential for male growth and fertility. Its mutations are responsible for androgen insensitivity syndrome (AIS) that usually shows the phenotype of azoospermia resulting in male infertility. This study reported the first case of mild AIS with complete normal serum hormones in a Chinese family. The proband referred for infertility because of azoospermia. His uncle and two cousins are both infertile and have azoospermia. Whole-exome sequencing in the genetic analyses showed that the proband carries a novel hemizygous AR missense mutation, NM_000044.6: c.2051G>C (p. Gly684Ala), in exon 4 within the ligand-binding domain. His mother and maternal aunt are heterozygous carriers, while his father and brother are wildtype, indicating that the mutation in the proband was inherited from his mother. This pattern is consistent with the genetic model of the X-linked recessive inheritance of AR in AIS pathogenesis. HOPE predicts that p. Gly684Ala increases the hydrophobicity of AR but does not change the AR conformation. PolyPhen-2 predicts that p. Gly684Ala is harmful. This study provides the new knowledge to understand the AR gene mutations in MAIS.